Konservering af en oldtidsmand - Lange-Kornbak, G. (Kuml, 1956)
Grauballe Man - The Conservation Process Grauballe Man was delivered to the conservation laboratory of the Forhistorisk Museum on Sunday, 27th April 1952, encased in the peat in which he was found, and during the following two days the overlying peat was carefully removed without disturbing the position of the body. During the pauses in this work the body was kept moist, by direct application of water and by covering with wet cloths and oilcloth, ordinary tap water being used without addition of chemicals. From Friday, 2nd May for ten days the peat-bog body was exhibited to large crowds. It was watered copiously before and after exhibition each day, and buckets and bowls of ice were set in and under the exhibition case to keep the exhibit moist and cool. The moisture was controlled by a hygrometer inside the case, and frequently registered 96 o/o. On one occasion, when small white larvae were noted in a patch of water on the body a ½ o/o solution of Phenol was applied by brush to the whole body except the lower half of the trunk, which was left untouched in order not to complicate future Carbon-14 dating. This application succeeded in preventing any further signs of deterioration of condition. After the exhibition a cast was made in plaster of paris of the bodies position on discovery. This cast proved of value later in providing a basis for exhibiting the subject in its original position and in revealing any incipient shrinking of the subject. For the making of the cast a ply-wood box was built around the body, any point likely to form a re-entrant was filled in with potter's clay, the body was brushed with glycerine to prevent adhesion, the hair covered for the same reason, and finally the plaster filled in. When the cast was made and the original position of the body safely recorded Grauballe Man was submerged on a wooden framework in a zinc tank full of tap water, to wait while the problem of conservation was studied. After a short trip to study the peat-bog bodies at Gottorp Castle and to discuss their conservation with the authorities of that museum, I proposed that Grauballe Man should be tanned. In making this suggestion I was influenced by the consideration that it was the humic and tannic acids in the peat that had conserved the body for nearly 2000 years, and that we had, in effect, a half-tanned subject on our hands. The post-mortem carried out on the body confirmed this view, on examination of the cross-section of skin thereby exposed. The directors of a tannery in Aarhus, after examining a specimen of skin, approved the suggestion and put me in touch with the Tannery Association's research laboratory at the Teknologisk Institut in Copenhagen. The laboratory confirmed the tanning process. P. Søndergaard, Master Tanner and member of the Jutland Archeological Society, thereafter acted as consultant to the process and on occasions as direct helper in its application. On 8th November 1952 the tanning process commenced, in a specially constructed watertight oak vat, 200 cms. long, 85 cms. wide and 110 cms. high. All metal parts were on the outside to prevent chemical reaction with the tannic acid and thereby the blackening of the subject. The bottom of the vat was filled with a mixture of 1/3 fresh oak bark to 2/3 oak bark soaked for 24 hrs. in ordinary water. The body was then laid on this filling, lying on its wooden frame and with the interior of the torso filled, by way of the post-mortem opening - with the same mixture. It was covered with a sheet to prevent marks by direct pressure from the bark and protected by a matress of shavings between the frame and the body, the whole being held together by broad canvas bands. The vat was then filled with oak bark in the above proportions and with ordinary tap water ½ ‰ Toxinol L added to prevent the formation of fungus growths on the surface. 200 kgs. bark and 1085 litres of water were used, the preparation standing to a depth of 100 cms. After 3 months, between 23rd and 27th February 1953, the solution was changed. During this changes Grauballe Man was examined by our consultant, who confirmed that the process was progressing satisfactorily, and that the skin was now evenly saturated with the tanning solution. The second solution, in use from 27th February to 20th October 1953, consisted of one third by volume of the bark used in the first solution mixed with 2/3 fresh bark, together with 500 litres of the first solution mixed with 500 litres produced by 24 hours' soaking of oak bark. Further Toxinol L was added to the solution. The third solution, in use from 20th October 1953 to 2nd June 1954, consisted of ¼ by volume of the bark used in the second solution, mixed with ¾ fresh bark, together with 565 litres of the second solution mixed with 240 litres produced by 48 hours' soaking of oak bark. ½ ‰ Toxinol L was again added. In all 875 kgs. of oak bark was used in the tanning process. On 2nd June 1954 Grauballe Man was removed from the tanning solution and washed clean of bark slime. Apart from the fact that the skin section in the torso now showed a completely homogeneous tanned state and that the skin was firmer, the body was unchanged in shape, appearance or colour. From 2nd June to 2nd July 1954 the subject lay in a solution of 10 % Turkish red oil in distilled water, and was then taken up to dry. As the water evaporated from the body a mixture of equal parts of glycerine, lanoline and cod-liver oil was applied, partly by brush and partly massaged into the skin, aided by warm air from a hair-dryer. The parts of the body which had best preserved their form, particularly the feet and one hand, were now given considerable injections of the German preparation Cellodal in order to preserve their shape. After two further applications of the oil mixture I was able to determine that the body was now stable. It was then prepared for exhibition. The organs of the body which had been removed for Carbon-14 dating and for stomach investigation were replaced by synthetic sponge rubber to reproduce the original shape, and the post-mortem incision was sewn together with nylon thread. The plaster cast, which was to form the exhibition base, was painted brown, coated with asphalt varnish and, while the varnish was still wet, strewn with pulverised peat. The body was then replaced in the cast and inserted in the teak and steel exhibition case presented by wellwishers. In this case it now lies, unchanged in position, size or colour from the moment when it was discovered in the peat bog at Grauballe. G. Lange-Kornbak